Corporate communication a guide to theory and practice - Cornelissen, Joep (SAGE, 2014)
Used by nearly 20,000 students in over 50 different countries on courses in Corporate Communication, Organizational Communication, PR and Marketing Communications and as an invaluable source for reflective practitioners, the new fourth edition has been updated to include topics such as the new media environment, CSR standards and corporate citizenship whilst retaining its practical yet strong theoretical approach.